OPPORTUNITIES AND CHALLENGES FOR IMPLEMENTING THE INDEPENDENT CAMPUS PROGRAM IN 3T REGIONS - Ade Risna Sari; Ramadha Yanti Parinduri; Jafar Sidik; Rieneke Ryke Kalalo; Bambang Sucipto (Indonesian Journal of Education (INJOE), 2023)
This research aims to; (1) knowing the opportunities for implementing independent campuses in 3T areas; and (2) knowing the challenges of implementing independent campuses in 3T areas. This research is qualitative research with descriptive methods. The data source used in this research is a library source. Researchers collected library sources to find out the opportunities and challenges of independent campuses in the 3T area. The data analysis technique used in this research is SWOT analysis. The results of this research show that; (1) Mapping opportunities for implementing MBKM on Teaching campuses in 3T areas shows opportunities for students to hone their skills before entering the world of work and opportunities for students to be able to develop and improve the quality of partner schools; and (2) the paradigm that occurs in practice shows that the implementation of the MBKM policy encounters various challenges, namely school facilities and infrastructure that do not meet standards such as difficulty in internet access and road access to schools in 3T areas, limited teacher competency, and students who take part in campus teaching programs. Most people who come to the 3T area come from outside the 3T area and are not familiar with the social and cultural conditions of the local area.